Ambient air nitrogen dioxide concentration and the growing incidence of asthma in school-aged children - P.N. Sari; D. Driejana; A.P. Yudison; D. Agustian; A.B. Kurnia; A. Riqqi (Global Journal of Environmental Science and Management, 2025)
BACKGROUND AND OBJECTIVES: Nitrogen dioxide, a significant air pollutant contributor to childhood asthma, is the focus of this study. In accordance with Sustainable Development Goals Target 3.9 and 11.6, this study plays a vital role in demonstrating the health effects of air pollution in developing nations, where such information is limited. The objectives of this study were to develop a more accurate early detection of nitrogen dioxide exposure related to asthma attacks to support more effective local asthma prevention and control strategies. This study explores the connection between nitrogen dioxide levels and asthma symptoms, including wheezing, in children residing in northeastern Bandung, Indonesia.METHODS: Palmes's passive diffusion tubes measured weekly nitrogen dioxide measurements at 83 sampling sites to obtain the spatial and temporal concentration variations. The employment of a 30 x 30 meters’ grid resolution model improved the accuracy of pollutant distribution, enabling consistent processing and interpretation of spatially resolved exposure data. The assessment of asthma symptoms was conducted using the International Study of Asthma and Allergies in Childhood questionnaire, administered to 842 individuals aged 6 to 12 years. The asthmatic children's residences were geocoded and linked to the modelled nitrogen dioxide concentration to assign individualized exposure values. Statistical analyses were performed to evaluate temporal trends, compare exposure groups, estimate wheezing risk, and assess spatial autocorrelation.FINDINGS: The weekly nitrogen dioxide concentrations were persistently high, with a mean of 110.87 ± 42.38 micrograms per cubic meter. Significant nitrogen dioxide concentration spatial variation was found across the study area (p < 0.001). Locations close to significant roads recorded the highest nitrogen dioxide concentrations, surpassing 120 micrograms per cubic meter. Forty-seven (5.6 percent) of the 842 children surveyed had experienced asthma attacks. Thirty-seven of the 47 children lived in areas where nitrogen dioxide exposure levels exceeded 100 micrograms per cubic meter, indicating a strong association between elevated nitrogen dioxide concentrations and asthma symptoms (p < 0.001). In the region with the highest concentration, children aged nine and above suffered from more asthma attacks (p = 0.026). Analysis results demonstrated that asthmatic children living near major roads correlated spatially with high nitrogen dioxide concentrations. More asthma attacks occurred during periods when nitrogen dioxide levels exceeded 120 micrograms per cubic meter. The robust spatial alignment with established evidence validates a persuasive relationship that bolsters causal inference.CONCLUSION: Children living near roadways are more prone to frequent asthma attacks. Apparent nitrogen dioxide concentration variations observed at fine spatial scales enable better detection of areas with elevated risk of asthma attacks, which provides detailed information for targeted health interventions. Future studies are being conducted based on these findings by incorporating longitudinal monitoring to gain a deeper understanding of causal pathways.